STRATEGI PENANGANAN ANCAMAN BIOTERORISME DI INDONESIA PASCA PANDEMI COVID-19 - Naila Ma'aliya; Agus Adriyanto; Triyoga Budi Prasetyo; Rudy Sutanto (CV. AFDIFAL MAJU BERKAH, 2023)
The Covid-19 pandemic has revived interest in the impact of using pathogens as weapons. Bioterrorism is the intentional release of viruses, bacteria or other agents used to cause disease or death in humans, animals or plants. There is the potential for state-sponsored terrorism against strategic targets and the potential for the use of biological agents in committing crimes that have no political goals but are committed for extortion or revenge. This study aims to analyze the threat of bioterrorism in Indonesia using a qualitative descriptive method. This study involved collecting data from various sources, such as related documents and reports, as well as interviews with relevant experts and stakeholders. The results of the study show that Indonesia is facing a real threat of bioterrorism which can endanger national defense and security as well as public health. Like Covid-19, even though it has been declared a pandemic, Covid-19 can also be called a bioterrorism threat even though it is not fully realized. Through this study, researchers want to show that threat identification in Indonesia still needs to be improved. This also needs to be accompanied by optimizing efforts to prevent and deal with bioterrorism, especially in the aspect of inter-agency coordination and increasing state intelligence capabilities. In supporting these efforts, regulations, human resources, technology and infrastructure need to be prepared as early as possible in order to deal with the threat of bioterrorism.